Refractive index of ferromagnetic semiconductors in a field of coherent light beams - Semchuk, O.Yu.; Semioshko, V.N.; Bila, R.V.; Magnus Willander; Magnus Karlsteen (Functional Materials, 2004)
The influence of intense laser radiation (coherent light beams (CLB)) on refractive index of a ferromagnetic semiconductor (FMSC) has been considered. It is shown that under CLB, in FMSC the grating of a refractive index takes place. A model explaining this effect is proposed. The relevant theoretical calculations have been carried out confirming the new phenomenon, appearance of refractive index grating in FMSC in a field of CLB. Рассмотрено влияние интенсивного лазерного облучения (когерентных световых пучков, КСП) на показатель преломления ферромагнитного полупроводника (ФМПП). Показано, что под воздействием КСП в ФМПП возникает решетка показателя преломления. Предложена модель для объяснения этого эффекта. Выполнены теоретические расчеты, подтверждающие наличие нового эффекта — появления решетки показателя преломления в ФМПП в поле КСП. Розглянуто вплив інтєнсивного лазерного опромінення (когерентних світлових пучків, КСП) на показник заломлення феромагнітного напівпровідника (ФМНП). Показано, що під впливом КСП в ФМНП виникає гратка показника заломлення. Запропоновано модель для пояснення цього ефекту. Виконано теоретичні розрахунки, які підтверджують наявність нового ефекту — виникнення гратка показника заломлення в ФМНП в полі КСП.